2019
DOI: 10.1111/chd.12784
|View full text |Cite
|
Sign up to set email alerts
|

Clinic nonattendance is associated with increased emergency department visits in adults with congenital heart disease

Abstract: Objective To determine the prevalence and predictors of nonattendance in an ACHD outpatient clinic, and to examine the relationship between nonattendance and emergency department (ED) visits, hospitalizations, and death. Methods Patients ≥ 18 years who had scheduled appointments at an ACHD outpatient clinic between August 1, 2014 and December 31, 2014 were included. The primary outcome of interest was nonattendance of the first scheduled appointment of the study period, defined as “no‐show” or “same‐day cancel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…Sporadic or recurrent nonattendance was unrelated to sex, age, diagnosis, ACHD AP group or socioeconomic group ( Table S1 ). Unlike others, we found no relationship between clinic nonattendance and emergency hospital admissions [ 16 ].…”
Section: Resultscontrasting
confidence: 99%
“…Sporadic or recurrent nonattendance was unrelated to sex, age, diagnosis, ACHD AP group or socioeconomic group ( Table S1 ). Unlike others, we found no relationship between clinic nonattendance and emergency hospital admissions [ 16 ].…”
Section: Resultscontrasting
confidence: 99%
“…A number of studies have reported no-show rates ranging from 4% to 80% in multiple clinical areas, including family medicine [ 39 – 41 ], general medicine [ 42 ], pediatrics [ 43 ], dermatology [ 44 , 45 ], cardiology [ 21 , 46 ], neurology [ 21 , 47 ], radiology [ 48 , 49 ], gastroenterology [ 50 , 51 ], ophthalmology [ 21 , 52 ], endocrinology [ 21 , 53 ], orthopedics [ 21 ], otolaryngology [ 21 , 54 , 55 ], plastic surgery [ 21 , 56 ], pulmonary [ 21 , 57 ], psychiatry [ 58 ], allergy [ 21 , 57 ], oncology [ 59 ], rheumatology [ 21 ], urogynecology [ 60 ], and urology [ 18 , 21 , 61 ]. The median prevalence of no-shows is lower in adult and pediatric primary care settings (< 20%) and higher in specialty care such as cardiology (30%), endocrinology (36%) and physiotherapy/physical therapy (57%).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the increasing frequency of acquired diseases such as diabetes or arterial hypertension also need strict pharmacological and non-pharmacological treatment (10)(11)(12). In general, in congenital heart disease medication non-adherence, as well as non-adherence to other therapeutic recommendations is associated with adverse outcome (13)(14)(15)(16). Adherence to medication has already been examined in chronic diseases and cardiac diseases other than congenital heart disease.…”
Section: Introductionmentioning
confidence: 99%